1991
DOI: 10.1128/aac.35.10.2042
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cefuroxime axetil suspension in infants and children

Abstract: The pharmacokinetics of cefuroxime axetil suspension in 28 infants and children, ranging in age from 3 months to 12 years (mean, 23 months), were studied. Mean maximum serum cefuroxime concentrations of 3.3, 5.1, and 7.0 ,ug/ml were achieved 3.6, 2.7, and 3.1 h after the administration of doses of 10, 15, and 20 mg, respectively, of cefuroxime axetil suspension per kg of body weight together with milk or milk formula. These concentrations exceed the MICs for common respiratory tract pathogens, including j8-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…Nascimento et al [14] reported a volume of distribution (V D ) of 0.19, 0.25 and 0.22 L/kg (mean 0.22 L/kg), which matched the V D of 0.21 L/kg (range 0.081 – 0.423 L/kg) reported by Knoderer et al [12]. Powell et al reported a half-life (t 1/2 ) of 1.9, 1.4, and 1.9 h (mean 1.75 h) which was similar to the t 1/2 of 1.8 h reported by del Rio et al [15, 17]. Therefore, a one-compartment PK model with first-order elimination was utilized.…”
Section: Methodssupporting
confidence: 79%
“…Nascimento et al [14] reported a volume of distribution (V D ) of 0.19, 0.25 and 0.22 L/kg (mean 0.22 L/kg), which matched the V D of 0.21 L/kg (range 0.081 – 0.423 L/kg) reported by Knoderer et al [12]. Powell et al reported a half-life (t 1/2 ) of 1.9, 1.4, and 1.9 h (mean 1.75 h) which was similar to the t 1/2 of 1.8 h reported by del Rio et al [15, 17]. Therefore, a one-compartment PK model with first-order elimination was utilized.…”
Section: Methodssupporting
confidence: 79%
“…After oral ingestion, cefuroxime axetil is deesterified in the intestinal mucosa and appears as cefuroxime in the blood. Peak concentrations in serum increase in proportion to dose and are 3.3 and 5.1 ,ug/ml after oral doses of a cefuroxime axetil suspension of 10 and 15 mg/kg of body weight, respectively (12). These results are comparable to those achieved in adults following administration of a 250-mg cefuroxime axetil tablet (7).…”
supporting
confidence: 74%
“…The pharmacokinetics of cefuroxime in infants and children following 10-, 15-, and 20-mg/kg doses of cefuroxime axetil suspension have been studied (23). A mean maximum cefuroxime concentration of 3.3 ,ug/ml was achieved in serum 3.6 h following a single 10-mg/kg dose of cefuroxime axetil suspension.…”
Section: Resultsmentioning
confidence: 99%